Epithelial sodium channel abundance is decreased by an unfolded protein response induced by hyperosmolality. Issue 11 (20th November 2014) - Crambert, Gilles; Ernandez, Thomas; Lamouroux, Christine; Roth, Isabelle; Dizin, Eva; Martin, Pierre‐Yves; Féraille, Eric; Hasler, Udo
Abstract Large shifts of osmolality occur in the kidney medulla as part of the urine concentrating mechanism. Hyperosmotic stress profoundly challenges cellular homeostasis and induces endoplasmic reticulum (ER) stress. Here, we examined the unfolded protein response (UPR) in hyperosmotically‐challenged principal cells of the kidney collecting duct (CD) and show its relevance in controlling epithelial sodium channel (ENaC) abundance, responsible for the final adjustment of Na+ excretion. Dehydration increases medullary but not cortical osmolality. Q‐PCR analysis of microdissected CD of water‐deprived mice revealed increased aquaporin‐2 (AQP2) expression in outer medullary and cortical CD while ENaC abundance decreased in outer medullary but not cortical CD. Immunoblotting, Q‐PCR and immunofluorescence revealed that hyperosmolality induced a transient ER stress‐like response both ex vivo and in cultured CD principal cells and increased activity of the canonical UPR mediators PERK and ATF6. Both hyperosmolality and chemical induction of ER stress decreased ENaC expression in vitro. ENaC depletion by either stimulus was abolished by transcriptional inhibition and by the chemical chaperone 4‐phenylbutyric acid and was partly abrogated by either PERK or ATF6 silencing. Our data suggest that induction of the UPR by hyperosmolality may help preserve body fluid homeostasis under conditions of dehydration by uncoupling AQP2 and ENaC abundance in outer medullary CD.